2022
DOI: 10.1136/bmjgh-2021-006803
|View full text |Cite
|
Sign up to set email alerts
|

Face mask mandates and risk compensation: an analysis of mobility data during the COVID-19 pandemic in Bangladesh

Abstract: IntroductionConcerns have been raised about the potential for risk compensation in the context of mask mandates for mitigating the spread of COVID-19. However, the debate about the presence or absence of risk compensation for universal mandatory mask-wearing rules—especially in the context of COVID-19—is not settled yet.MethodsMobility is used as a proxy for risky behaviour before and after the mask mandates. Two sets of regressions are estimated to decipher (any) risk-compensating effect of mask mandate in Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
2
12
1
Order By: Relevance
“…One of the concerns with public health measures is that individuals who undertake these measures may engage in a higher risk behavior, believing that they are protected, thereby removing the benefits of the measures. The results of this study refute this theory of risk compensation; 28 , 29 participants more in favors of the protective measures were also the ones with better intention to get vaccinated.…”
Section: Discussionsupporting
confidence: 59%
“…One of the concerns with public health measures is that individuals who undertake these measures may engage in a higher risk behavior, believing that they are protected, thereby removing the benefits of the measures. The results of this study refute this theory of risk compensation; 28 , 29 participants more in favors of the protective measures were also the ones with better intention to get vaccinated.…”
Section: Discussionsupporting
confidence: 59%
“…The risk compensation theory suggests that people adjust their behaviour in response to perceived levels of risk and become more careful where they sense greater risk [67][68][69][70][71]. A few studies found no evidence of risk compensation during the pandemic [56,68,72], but our findings suggest it exists like it does in Bangladesh [56]. This finding may have implications for health education on the use of COVID-19 control measures.…”
Section: Discussioncontrasting
confidence: 44%
“…This may reflect high risk-taking nature of individuals who had symptoms of COVID-19 but did not get tested which would explain the poor physical distancing practices. Risk-takers have lower COVID-19 precautionary index [56]. However, it does not explain the higher odds of working remotely.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Mandatory mask wearing might have created a sense of safety among the public which led to the decrease in the amount of time spent at home. Wadud et al discuss the risk compensation effects of mandatory mask wearing rules in further detail ( 29 ).…”
Section: Resultsmentioning
confidence: 99%